Immune Cells in Subretinal Wound Healing and Fibrosis - Szczepan, Manon; Llorián-Salvador, María; Chen, Mei; Xu, Heping (Frontiers in Cellular Neuroscience, 2022)
The subretinal space is devoid of any immune cells under normal conditions and is an immune-privileged site. When photoreceptors and/or retinal pigment epithelial cells suffer from an injury, a wound healing process will be initiated. Retinal microglia and the complement system, as the first line of retinal defence, are activated to participate in the wound healing process. If the injury is severe or persists for a prolonged period, they may fail to heal the damage and circulating immune cells will be summoned leading to chronic inflammation and abnormal wound healing, i.e., subretinal or intraretinal fibrosis, a sight-threatening condition frequently observed in age-related macular degeneration and recurrent uveoretinitis. Here, we discussed the principles of subretinal wound healing with a strong focus on the conditions whereby the damage is beyond the healing capacity of the retinal defence system and highlighted the roles of circulating immune cells in subretinal wound healing and fibrosis.